PENGARUH PERPUTARAN PERSEDIAAN TERHADAP MODAL KERJA (STUDI KASUS PADA PT. UNILEVER INDONESIA TBK. YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2006-2013) - Kurniawan, Iwan (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2020)
This research purposed to determine the Inventory turn over, the working capital and the influence of inventory turnover of working capital in PT. Unilever Indonesia Tbk. listed on the Indonesia Stock Exchange. Variables used in this study is inventory turnover, and working capital. The sample used is a quarterly financial report on PT. Unilever Indonesia Tbk. the period 2006-2013, the number of samples in this study are 32 samples. The analysis used is simple linear regression. This analysis is used to determine the partial significant, coefficient of determination test and t test. Simple linear regression test results obtained Y = 179,852.014 + (-122,077.337 X) containing the sense that at the time of inventory turnover rate among the working capital turnover rate (Y) is at 179,852.014. Test showed that the coefficient determinant to yield 4.3% whereas the t test if thitung < t tabel (-1.154 <2.042), the hypothesis Ho received Ha refused to see its significance, see yields ttabel statistical significance at 5% level of the sig = 0.257> 0 , 05 (5%). which means there is no influence of inventory turnover for working capital.